GERD : more than just heartburn - Information Television Network ([Boca Raton, FL] : Information Television Network, 2006)
Series content includes timely, topical, accurate information necessary for making informed choices so patients and families can work collaboratively with their doctors making them better prepared to be a partner in their own cure.
Title from container.
Title lacks production credits.
Home Use.
E.
DVD.
108012
Keywords: Gastroesophageal reflux; Heartburn; Instructional films; Videodiscs